Small mammals and microhabitat selection in forest fragments in the transition zone between Atlantic Forest and Pampa biome - Skupien, Fabrício Luiz; Rodrigues, Daniele Pereira; Sausen, Jady de Oliveira; Gonçalves, Gislene Lopes; Lima, Daniela Oliveira de (Papéis Avulsos de Zoologia, 2022)
Natural resources are depleted in fragmented landscapes that have their vegetation also altered. As a result, the microhabitat diversity and the composition and distribution of local species are affected. In this study, we evaluated the small mammals' community diversity, composition and microhabitat selection in two Atlantic Forest fragments, in an ecotone area with the Pampa biome, southern Brazil. We recorded five rodents (Akodon montensis, Oligoryzomys nigripes, Sooretamys angouya, Juliomys pictipes and the exotic Rattus rattus) and one marsupial (Didelphis albiventris). Both fragments were dominated by the generalist rodent A. montensis. Akodon montensis and O. nigripes showed similar habitat preferences: ground covered by rocks and higher values of vegetation obstruction. Sooretamys angouya preferred places with higher abundance of trees. Fruit availability was important for A. montensis and D. albiventris, highlighting the importance of this food resource for local wildlife, and the potential role of these species as seed predators and dispersers. Small species richness, the presence of an exotic species and high dominance level suggest that the study area is highly degraded.